Unveiling Figures of Speech and Diction in “Stecu Stecu” by Faris Adam: A Stylistic Analysis - Sutardi Sutardi; Aristya Kumala (Edulitics (Education, Literature, and Linguistics) Journal, 2024)
This study investigates the use of figures of speech and diction in the lyrics of “Stecu Stecu” by Faris Adam as a widespread, popular, and distinctive lyrical style that reflects emotional expression and cultural identity, using a stylistic approach. The study aims to identify the types of figures of speech used in the lyrics, analyze the forms and functions of diction, and examine how these stylistic elements contribute to the construction of meaning and cultural representation. This research employed a descriptive qualitative method using content analysis techniques. The data consisted of words, phrases, and expressions from the song lyrics, which were analyzed using stylistic theory. The analysis focused on identifying figurative language, examining diction, and interpreting the cultural meanings embedded in the lyrics. The findings reveal that the lyrics employ several dominant figures of speech, including metaphor, hyperbole, personification, and repetition, which serve to heighten emotional intensity and aesthetic expression. In addition, the song's diction features colloquial and regional expressions associated with Ambonese and Maluku cultural identity. These linguistic choices create authenticity, emotional closeness, and cultural representation within the lyrics. The study also found that figures of speech and diction work synergistically in conveying social values, emotional experiences, and local cultural perspectives. Overall, the findings indicate that contemporary popular songs can function not only as entertainment but also as literary and cultural texts rich in stylistic and sociocultural meaning. This study contributes to stylistic research by highlighting the relationship between figurative language, diction, and cultural representation in Indonesian popular music.